2014
DOI: 10.1016/j.socscimed.2014.01.054
|View full text |Cite
|
Sign up to set email alerts
|

Barriers in access to healthcare in countries with different health systems. A cross-sectional study in municipalities of central Colombia and north-eastern Brazil

Abstract: There are few comprehensive studies available on barriers encountered from the initial seeking of healthcare through to the resolution of the health problem; in other words, on access in its broad domain. For Colombia and Brazil, countries with different healthcare systems but common stated principles, there have been no such analyses to date. This paper compares factors that influence access in its broad domain in two municipalities of each country, by means of a cross-sectional study based on a survey of a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0
23

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(96 citation statements)
references
References 23 publications
4
69
0
23
Order By: Relevance
“…Garcia-Subirats et al 26 found similar results, that is, socioeconomic differences in resolution of health problems and initial health care-seeking in a large city in Brazil. Previous studies 4,28,35 showed that use of the private sector was more frequent among higher socioeconomic groups.…”
Section: Access Use and Quality Of Health Care Services And Trends mentioning
confidence: 67%
See 1 more Smart Citation
“…Garcia-Subirats et al 26 found similar results, that is, socioeconomic differences in resolution of health problems and initial health care-seeking in a large city in Brazil. Previous studies 4,28,35 showed that use of the private sector was more frequent among higher socioeconomic groups.…”
Section: Access Use and Quality Of Health Care Services And Trends mentioning
confidence: 67%
“…Brazil has major socioeconomic inequalities in health, with the most adverse health outcomes occurring among the poorest segments of the population 4 . Inequalities in the health system could explain part of these socioeconomic inequalities in health 26 . Inequalities in socioeconomic factors can also result in socioeconomic inequalities in health, i.e.…”
Section: Access Use and Quality Of Health Care Services And Trends mentioning
confidence: 99%
“…(25), pues analiza las barreras en distintas etapas del acceso, incluyendo el momento en el cual las personas inician la búsqueda. Según este estudio, las principales barreras se dan tanto en el acceso inicial como en la continuación a solucionar los problemas de salud, y constituyen en su mayoría barreras de tipo geográfico, econó-mico y las relacionadas con las autorizaciones por parte de las eps.…”
unclassified
“…Las dificultades anteriormente mencionadas que reconocieron los participantes, coinciden con lo identificado en el estudio realizado por García-Subirats, et., al, en el que se analizan los diferentes obstáculos de acceso a los servicios de salud y se establece que las barreras de tipo geográfico, económico y las relacionadas con las autorizaciones por parte de las EPS, son las principales limitantes de la atención (19) .…”
Section: Discussionunclassified